The impact of physical activity taster sessions on barriers and facilitators to long-term physical activity behaviour - Darren Richardson; Emma Eyre; Nikki Holliday; David Broom; Michael Duncan; Matthew Hill; William Donald; Jason Tallis (Asian Journal of Sport and Exercise Psychology)
Epidemiological evidence suggests that physical activity (PA) can improve the health, physical function and the quality of life of older adults. Several modes of PA have been highlighted as particularly beneficial for these outcomes, but the challenges of engaging and sustaining participation limit their effectiveness. Therefore, the aim of this study was to determine barriers and opinions to regularly engaging in different types of PA using taster sessions to provide recommendations on how to engage and sustain PA behaviour in older adults. A multi-phase, mixed-method study design on 12 older adults was used to gain insight into older adult's perceptions of five types of PA (two sports, resistance exercise, exergaming, yoga and home-based exercise). Perceptions of these types of PA were collected pre-taster sessions and were re-evaluated after all taster sessions using questionnaires and focus groups. Triangulation of data revealed that in general, all PA types were enjoyed, but yoga was least popular. Pre-taster sessions, home-based exercise and resistance exercise were most popular whereas following the taster sessions, preferences were for exergaming, resistance exercise and sports. Our data highlights the effective utility of taster sessions and combined with other literature; we present several key recommendations to help to improve engagement in long-term PA behaviour in various PA types. These include ensuring adequate social interaction between similarly aged and ability capable older adults during PA. Having appropriate supervisors, and advertising and facilitating PA opportunities, considering the needs of individuals, providing motivational strategies and providing continued accountability.